ENOSIS, BLOODY CHRISTMAS AND ALBANIAN SUPPORT TO TURKEY ON CYPRUS QUESTION IN THE UNITED NATIONS - Ali ÖZKAN (Fırat University, 2019)
The national interest of the Imperialist countries always comprises Turkey becuase of her geographical and strategic location. The imperialist states which are unwilling to see a very powerful Turkey have targeted to create lots of inner and outsider problems for Turkey. Additionally, they especially wanted to have Turkey get into conflict with her neighbouring and regional states. The created Cyprus problem between Turkey and Greece was one of the significance examples regarding to this description The thought of having Cyprus become a part of Greece(Enosis) and killing all Turks who have been living in Cyprus constituted one of the most crucial elements of Greece’s Megali Idea. To realize this idea especially durgin the period of Archbishop Makarios III, the Greek Cypriots massacred the Turks by the end of 1963. This event has passed as Bloody Christmas Events within the history of Cyprus. As the main responsible person of Bloody Christmas Events Makarios III aimed at three things. The first one was to create Bloody Christmas Events fort he sake of realizing the Enosis regardless the Cyprus Republi which was established due to the agreements made by Turkey, Greece and UK within the years of 1959 and 1960. Secondly, whenever getting no result in 1963 Bloody Christmas Events, it was the time to handover the issue to the United Nations. The third one was to reduce the effectiveness of Turkey on Cyprus. Five countries were found on the supporting decision of the United Nation on this subject in 1965. One of those countries were Albania. In this article, Enosis as a part of Megali Idea, Bloody Christmas Events and the reason and the reflection of the support of Albania to Turkey on the problem of Cyprus in the United Nations although it was ruled by communist regime will be examined in details.